DESCRIPTION OF BIOLOGICAL AGE ESTIMATION WITH THE DEMIRJIAN METHOD USING DIGITAL PANORAMIC RADIOGRAPHY IN SEMARANG - Niluh Ringga Woroprobosari; Adisty Restu Poetri; Hamizul Fuad (Jurnal Medali, 2022)
Background: Age estimation is forensic science to help victims of disasters, accidents, or criminal cases. Age estimation using panoramic radiographs can be an option. The use of panoramic radiographs in age estimation requiring some methods, one of them is Demirjian method. The assement of tooth age by the Demirjian method is based of the tooth maturation process approach as the indicator.This study aim was to determine the description of biological age estimation using the Demirjian method in the city of Semarang.Method:The design of this research was a cross-sectional study with a total sample 152 (71 boys and 81 girls). The estimated age of the Demirjian method used 7 left mandibular teeth except for the third molar. The age assessment was based on 8 stages of crown calcification to the root, after each tooth score has been added and the maturation score is calculated, and subsequent maturation scores are converted into the age of the tooth to determine the age of 3-16 years. Data analysis using the SPSS program and analyzed by descriptive test.Result: The results obtained by the average difference in biological age and chronological age was 1.1 years and there was 87 data that under estimation, 57 data over estimation, and 8 data on estimation.Conclusion: The depiction of biological age in Semarang, the age group between 3-26 years the average Demirjian method is 1.1 years.